Comparison of the Efficacy of Intrathecal Fentanyl 20mcg versus Intrathecal Morphine 0.2 mg as an adjuvant therapy in spinal anesthesia in lower limb surgery - May, Lee Jun (2020)
Background Spinal anesthesia is the preferred method of anesthesia for majority of the lower limb surgery. Intrathecal Morphine is an adjuvant used to provide prolonged analgesia post operatively. The objective of this study was to investigate the efficacy of adding Intrathecal morphine 0.2mg by assessing the analgesic effect 24hours post spinal anesthesia and to assess the proportion of complication that ensues. Methods 43 patients scheduled for various lower limb orthopedic surgery were studied in a prospective, single blinded controlled clinical trial. They were divided into 2 groups; Patient in ITF group receive 2.8mls of 0.5% hyperbaric bupivacaine with 20mcg of fentanyl added whilst patient in ITM group received 2.8mls of 0.5% hyperbaric bupivacaine with 0.2 mg of morphine added. The primary outcome was the pain score within 24 hours post operatively while the secondary endpoint was to determine the proportion of complications (nausea, vomiting, pruritus sedation and respiratory depression between the 2 groups. Results: Intrathecal morphine group revealed significantly lower median pain score at 6th, 12th, 18th and 24th hour post op. There was a significant difference in VAS score between the ITF and ITM group over 24 hours post operatively. There is no difference in terms of incidence of nausea between 2 groups (p=0.098), higher incidence of vomiting (n=9, 39.1%, p=0.002 ) and pruritus (n=10, 43.5%, p=0.001) in ITM group, No incidence of respiratory depression was recorded in both ITF and ITM group. Conclusion: Intrathecal morphine 0.2 mg as an adjuvant to spinal anesthesia provided prolonged 24 hours analgesia with no respiratory depression but at the expense of increased vomiting and pruritus which can be prophylactically treated with antiemetics.